an empirical study of Credit Policy Determinants of Algerian Banks/ During the period (1989-2009) - Abadi, Mohamed (Milev Journal of Research and Studies, 2023)
The study aimed to test the effect of size of deposits, the real interest rate, population, economic reforms on the credit policy of commercial banks of Algeria represented by the size of credit facilities. The study Used annual data for the period from 1989 to 2009. Where the Multi regression model was estimated using a method of Ordinary Least Squares OLS. Results of the analysis showed that there is a positive relationship with a statistically significant between the credit facilities and the deposits and the variable of economic reforms, while the real interest rate and population size have been linked by significant negative relationship